Isolation of Silica from Some Species of Diatoms in Iraqi Water - Shaimaa Setae M. Ali (Journal of Global Pharma Technology, 2016)
We obtained these diatoms species growth from diatoms (Nitechia acuta, cocconeis pediculus, Nit dissipata, stephanodiscus astrea, syndra ulna, Diploneis).According to scanning electron microscope, the SiO 2 morphologies of having microspores and fibers in the surface of 59.81 m 2 /g. All results refer that the basilica specimens get found in this study. The prepared basilica material having Porous structures which its ability, it can be used in other industrial applications.